Formação médica com adoção de metodologia ativa de ensino: considerações individuais e reflexivas sobre o processo - Galego, Lucas dos Santos (Universidade Federal de São Carlos, 2024)
Introduction: This work is built in an autobiographical and critical-reflective narrative about the medical course of the Federal University of São Carlos, presenting the facilities and difficulties of self-directed learning proposed by the institution, its importance as a methodology and some points that can be improved according to the author's opinion based on the experiences lived. Objective: To expose facts and opinions about constructivist method and its application in the medical course of UFSCar, generate reflections on how it is put into practice and how students perceive it. Method: The methodology used for this course completion work consists of personal accounts and a literature review with the consultation of electronic materials found on SCiELO and PubMed regarding the constructivist methodology Conclusions: It is possible to conclude that there was an important effort of the medical course Universidade Federal de São Carlos to remain faithful to the constructivist method based on problems. However, not all, despite their desire, fully adapted to the method, resulting in insecurities generated by the lack of support from other pedagogical-methodological approaches.
Medical training with the adoption of active teaching methodology: individual and reflective consideration about the process
Keywords: Aprendizagem Baseada em Problemas; Educação Médica; Problem-Based Learning; Medical Education; CIENCIAS HUMANAS::EDUCACAO::CURRICULO